Virtual Environment for Training and Skill Enhancement for Offshore Workers - Muhammad Zamzuri, Nur Nabila Ashykin (Universiti Teknologi PETRONAS, 2020)
The objective of this project is to design and develop a virtual offshore environment as a method for immersive and competent based learning and training where the offshore workers can perform realistic activities in a virtual environment without risking their health and production of the facilities. In the development of the virtual environment, this project emphasized the features and functionalities of a gaming development software called Unity 3D that functions as the platform to create a realtime environment of the offshore platform. It is noted that current training methods in the oil and gas industry have not been fully sufficient in preparing the offshore workers to go through a complex and dangerous realistic work environment on the offshore platform. Furthermore, the development of this project is to encourage the productivity of the immersive virtual training contents through simulation training by the offshore workers alongside their performance during the training plus to help in minimizing the risks and costs associated with the oil and gas operations.